Oil and gas corporations as anti-racist decolonial liberators? A case study of propaganda from the struggle against Shell in South Africa - Alex Lenferna (Journal of Political Ecology, 2024)
Oil and gas corporations and their lobbyists are increasingly appropriating the language of racial justice, anti-imperialism, and decolonization to block climate action and advance a polluting, extractive, and neocolonial agenda. This article argues that these appropriations are a form of propaganda called 'undermining demagoguery', which serves to subvert the very ideals it claims to uphold. Shell's attempt to explore for oil and gas off the Wild Coast of South Africa is used as a case study. The article shows how such propaganda efforts are becoming increasingly prevalent and recommends strategies that can be used to counteract them.